MANAJEMEN PROGRAM JURNAL PAGI UNTUK MENGUATKAN KESIAPAN BELAJAR PADA ANAK DI TK DIPONEGORO 111 AJIBARANG BANYUMAS - Nurochmah; Novan Ardy Wiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the management of the Morning Journal program in strengthening the learning readiness of early childhood students at TK Diponegoro 111 Ajibarang Banyumas. The Morning Journal program is an initial classroom activity conducted before the core lessons, involving greetings, storytelling, singing, and light dialogue between teachers and students. This research used a qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that the management of the Morning Journal program which includes planning, implementation, and evaluation is carried out systematically and purposefully. Teachers play an active role in creating an enjoyable atmosphere that supports children's emotional and social development. The program effectively enhances children's concentration, confidence, and cooperative behavior during learning activities. Therefore, the Morning Journal program serves as an essential strategy in early childhood education to foster holistic learning readiness.Keywords: Learning management, morning journal, learning readiness, early childhood, kindergarten education.